Near‐Unity Quantum Yields from Chloride Treated CdTe Colloidal Quantum Dots. Issue 13 (27th October 2014) - Page, Robert C.; Espinobarro‐Velazquez, Daniel; Leontiadou, Marina A.; Smith, Charles; Lewis, Edward A.; Haigh, Sarah J.; Li, Chen; Radtke, Hanna; Pengpad, Atip; Bondino, Federica; Magnano, Elena; Pis, Igor; et al.
<x xml:space="preserve">Abstract</x> Colloidal quantum dots (CQDs) are promising materials for novel light sources and solar energy conversion. However, trap states associated with the CQD surface can produce non‐radiative charge recombination that significantly reduces device performance. Here a facile post‐synthetic treatment of CdTe CQDs is demonstrated that uses chloride ions to achieve near‐complete suppression of surface trapping, resulting in an increase of photoluminescence (PL) quantum yield (QY) from ca. 5% to up to 97.2 ± 2.5%. The effect of the treatment is characterised by absorption and PL spectroscopy, PL decay, scanning transmission electron microscopy, X‐ray diffraction and X‐ray photoelectron spectroscopy. This process also dramatically improves the air‐stability of the CQDs: before treatment the PL is largely quenched after 1 hour of air‐exposure, whilst the treated samples showed a PL QY of nearly 50% after more than 12 hours.